Interaction of Overweight and Pronated Foot on Ground Reaction Force Frequency Content During Running - Amirali Jafarnezhadgero; Ehsan Fakhri Mirzanag; Hamed Sheikhalizadeh; Hamed Parsa (Pamukkale University, 2024)
Being overweight can influence the occurrence of pronated feet (PF). This research aimed to assess the interaction effect of overweight and PF along with sex on the frequency content of ground reaction forces (GRFs). 104 young male and female adults were allocated to four groups: normal body-mass-index/normal feet, normal body-mass-index/PF, excessive weight/normal feet, and excessive weight/PF. Subjects ran at constant speed over the walkway while an embedded force plate was located at the midpoint of the walkway. GRFs were recorded during 20 running trials. Findings demonstrated the significant main effect of "sex" (P